Morphogenetic basis of the unified state register of soil resources of Russia - V. S. Stolbovoy; E. N. Molchanov; B. V. Sheremet (Бюллетень Почвенного института им. В.В. Докучаева)
Nomenclature and taxonomic diversity of soils and their horizon-profile diagnostics/descriptions define morphogenetic soil indicators used in the Unified State Register of Soil Resources of Russia (with Russian abbreviation of EGRPR). Most of these soil indicators are of non-metric origin, i.e., established conventionally by agreement. Subject area of soil science includes a hierarchy of 5 types of soil objects (pit, profile, horizon, morphological element and sample), 380 indicators, 607 methods and 3019 values of the indicators.